Tracking the Expression of Photosensitive Genic Male Sterility Gene in Rice - Njiruh, Nthakanio P.; Xue, Qingzhong (My University, 2013)
Photoperiod sensitive genic male sterile rice lines contain genes that induce complete male sterility in high temperature and long day light length period, but are male fertile under low temperature and short day light length growth conditions. These lines are good candidates for hybrid rice seed production. The main challenge limiting their use in production of hybrid rice seeds is that of determining the exact time of their growth period when sterility gene(s) is completely expressed. Knowledge of this will enable development of a breeding program that ensures that sterility inducing conditions prevail in critical sterility point. The objective of this study was, therefore, to determine the time in the rice growth period when the sterility gene(s) are expressed. Rice line ZAU11S106, a Photoperiod sensitive genic male sterile line, was used to test hypothesis that it is possible to estimate time within 48hours when PGMS gene is expressed. Sowing was done in 8rows in Hangzhou-China, so that plants matured in August when day light length was over 14hours and day temperatures were over 30°C. At 57days old plants in row one were given short day light length treatment while plants in row two were given the treatment when they were 61days old or 4days later. After every four days the next row was included in the treatment. This was done until the plants in row one flowered when the treatment was stopped. Plants given short day length treatment at 73 and 77 days old realized 6% and 0% seed set respectively. At 73 and 77 days old the plants were at dyad and tetrad stages of pollen development 2 respectively. The conclusion was that, the sterility gene was observed to be expressed within 48hours (four days) lying within 73 and 77 days or within the dyad and tetrad stages of pollen development.
Keywords: Meiosis; Photoperiod; Pollen abortion; PGMS rice